Effect of processing parameters on quality attributes of cream cheese - Debnath, Anindita (Indian Journal of Dairy Science, 2017)
Abstract Cream cheese with a desirable sensorial as well as textural attributes were prepared from buffalo milk with some modification to meet the consumers’ expectation. To develop it, method for preparing cream cheese, type of starter culture for acidification of milk, type of stabilizer with their proper concentration was selected and the processing parameters like standardization of milk fat, pasteurization temperature as well as cooking temperature were optimized on the basis of sensory evaluation and textural property. The cold pack method was selected as the best suited method for preparing cream cheese when, NCDC-275 culture and carboxy methyl cellulose at the concentration of 0.3% provide improved flavour as well as body and texture score. Based on sensorial appeal milk fat percentage, milk pasteurization temperature and curd cooking temperature was selected within the range of 10-12%, 75-85˚C and 50-70˚C, respectively.